English in the World before and Today - Nigina Juraboeva (Researchparks Publishing, 2023)
In the last few decades, English has emerged as the pre-eminent language for international communication. It is spoken by more people around the world than any other language, and is regularly described as a truly ‘global’ language. In this article the role that English plays in the world today, and examines the social, political and cultural factors that have influenced its development is illustrated. It traces the history of the language from its arrival in Britain in the fifth century AD through to the present day and its status as a language with a truly global reach. It looks at how and why English came to occupy this position, and at what the consequences of its global spread are for the way it’s used and perceived around the world.